How to Feed the Mammalian Gut Microbiota: Bacterial and Metabolic Modulation by Dietary Fibers - Ferrario, Chiara; Statello, Rosario; Carnevali, Luca; Mancabelli, Leonardo; Milani, Christian; Mangifesta, Marta; Duranti, Sabrina; Lugli, Gabriele A.; Jimenez, Beatriz; Lodge, Samantha; Viappiani, Alice; Alessandri, Giulia; et al. (Frontiers in Microbiology, 2017)
The composition of the gut microbiota of mammals is greatly influenced by diet. Therefore, evaluation of different food ingredients that may promote changes in the gut microbiota composition is an attractive approach to treat microbiota disturbances. In this study, three dietary fibers, such as inulin (10 %), resistant starch (10 %) and citrus pectin (3 %), were employed as supplements to normal chow diet of adult male rats for two weeks. Fecal microbiota composition and corresponding metabolite profiles were assessed before and after prebiotics supplementation. A general increase in the Bacteroidetes phylum was detected with a concurrent reduction in Firmicutes, in particular for inulin and resistant starch experiments, while additional changes in the microbiota composition were evident at lower taxonomic levels for all the three substrates. Such modifications in the microbiota composition were correlated with changes in metabolic profiles of animals, in particular changes in acetate and succinate levels. This study represents a first attempt to modulate selectively the abundance and/or metabolic activity of various members of the gut microbiota by means of dietary fibers.